Effect of modified materials on the hydraulic conductivity of loess soil - Lina Guo; Yongbo Zhang; Hong Shi; Qing Duan; Shuyuan Xu; Wenjing Qin; Zhixia Duan (Scientific Reports)
Abstract The natural clay resources that filled the impermeability requirement in the Loess Plateau are scarce. Therefore, it is necessary to modify loess soil to meet the requirements of landfill barriers. In this study, an experimental study was performed to determine the effect of different application rates (1%, 3%, and 7%) of fly ash, nano silica sol, and nanoclay amendments on the hydraulic conductivity of loess. Also, X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), scanning electron microscope (SEM), Brunaer-Emmett-Teller (BET), and Computed tomography (CT) procedures were carried out to analyze the underlying mechanisms of modified materials affecting hydraulic conductivity of loess. The results showed that the addition of modifiers, especially nanoclay, reduced the hydraulic conductivity of loess soil (2.7 × 10−6cm s−1) significantly, and the saturated hydraulic conductivity were respectively 2.7 × 10−6cm s−1, 1.0 × 10−6cm s−1, 1.4 × 10−7cm s−1 and 8.0 × 10-8cm s−1 for modified loess soil with 7% fly ash, 7% nano silica and 7% nanoclay, which were 62.96%, 94.81%, and 97.07% lower than natural loess soil. Modified loess soil with 7% nanoclay had a saturated permeability coefficient of 8.0 × 10−8 cm s−1, meeting the anti-seepage standards of the domestic waste landfill liner. The microstructure and surface properties of loess improved obviously after being treated with modified materials. XRD, FTIR, and SEM test results showed that the modifier particles and byproducts of pozzolanic reaction filled the interstices between particles, which could reduce the porosity and improve the bonding strength of the soil particles. The CT procedures showed the nanoclay has a significant effect on the distribution of pores and characteristics of pore throat, which led to the reduction of the effective seepage path in soil, and further decreased the hydraulic conductivity of loess soil. The research provides a fundamental base for the development of loess foundation modification technology and possesses important implications for utilizing loess resources synthetically in accordance with local conditions.